Dead on the table: A theoretical expansion of the vicarious trauma that operating room clinicians experience when their patients die. Issue 5 (28th May 2019) - Hartley, Heather; Wright, David Kenneth; Vanderspank-Wright, Brandi; Grassau, Pamela; Murray, Mary Ann
Abstract: The practice of operating room (OR) clinicians – nurses, surgeons, and anesthetists – is fundamentally about preserving life. Some patients, however, die in the OR. Clinicians are therefore vulnerable to moral and emotional trauma. In this paper, we discuss three forces that shape clinicians' moral and emotional experiences in OR care: biomedical values, normative death discourse, and socially (un)sanctioned grief. We suggest how each of these forces increases clinicians' vulnerability to feel traumatized when their patients die. We hope this discussion will stimulate clinicians and researchers to engage with social and cultural determinants of clinicians' experiences when patients die.